A Survey of Network and Information Security - Huang Jie (University of Respati Yogyakarta, Indonesia, 2019)
Security threats and shows abnormality about security, safety, privacy and trust as network security-related data, in short, security-related data. Apparently, the first step to detect network attacks and intrusions is to collect the security-related data. In this paper, we will present a lot of approaches to solving Networks and Information Security issues. We survey network security in LTE technologies, Vehicular Ad-Hoc Network, and security in Wireless Sensor Network. Internet of Things. In this paper, we describe many methods in Information Security. Is consist of Information Security in Big Data and Cloud Computing.